2017
DOI: 10.1515/jcim-2016-0130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of hypoglycemic and hypolipidemic activity of various extract of Anogeissus latifolia bark in streptozotocin-induced diabetic rats

Abstract: Background Anogeissus latifolia Wall. (A. latifolia) bark has been traditionally used in the treatment of various diseases which includes diabetes and general debility. The present study was aimed to investigate the comparative hypoglycemic and hypolipidemic activity of various extracts of A. latifolia bark in streptozotocin-induced type 1 diabetic rats. Methods Acute toxicity was carried out at 2 g/kg dose of petroleum ether extract of A. latifolia bark (PEALB), chloroform extract of A. latifolia bark (CEALB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Research conducted by Affini and Surip [6] showed that job satisfaction directly affects employee engagement. The study results are consistent with research conducted by Kattili et al [7] that showed that job satisfaction positively affects employee engagement (Fig. 1).…”
Section: Introductionsupporting
confidence: 92%
“…Research conducted by Affini and Surip [6] showed that job satisfaction directly affects employee engagement. The study results are consistent with research conducted by Kattili et al [7] that showed that job satisfaction positively affects employee engagement (Fig. 1).…”
Section: Introductionsupporting
confidence: 92%
“…In view of the adverse effects associated with the synthetic drugs and as plants are safer, cheaper and much effective, conventional antidiabetic plants can be explored [4]. Over 400 traditional plants have been reported for the treatments of diabetes [5]. Furthermore, after the World Health Organization recommended, investigation of hypoglycemic agents from medicinal plants has become more important [6].…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies have demonstrated that STZ injection significantly reduces body weight, which is associated with an increase in serum glucose level and impaired insulin and lipid profiles. 19 In this study, SOD activity levels in the serum and liver of diabetic rats were decreased significantly compared to the control group, but a significant dosage-dependent increase was observed in the diabetic rats treated with PG compared to the control group. STZ-induced diabetes exacerbated tissue damage by reducing the activity of endogenous antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 48%